(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To determine the functional outcome of the muscle slide technique in patients with Volkmann’s ischemic contracture. Methodology: Upon clinical presentation, a consultant orthopaedic surgeon diagnosed forty-three patients with severe Volkmann ischemia contracture. The sample size was determined using the WHO Sample Size calculator using the parameters of a 5% significance level, margin of error of 15%, and success rate of 47.70% for the muscle slide method. Clinical evaluation in terms of functionality was done before and after the muscle slide procedure in the 3rd and 6th week post operation. Results: As per functional outcomes of muscle slide procedure, 26 (60.5%) patients had excellent, 6 (14.0%) had good, 7 (16.3%) had fair, and 4 (9.3%) patients had poor functional outcomes. Conclusion: Muscle slide technique is an effective technique in robustly managing Volkmann’s ischemic contracture.